Desain UI/UX Aplikasi E-commerce Berbasis Mobile untuk Bengkel Roda Mas Memanfaatkan Figma dengan Metode User Centered Design - Bakti, Ahmad Mutatkin; Marshandi, Fito (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
User Interface (UI) design and User Experience (UX) play a crucial role in the success of digital applications, particularly mobile-based e-commerce platforms. Good and effective design is characterized by constrasting yet harmonious color choices, intuitive navigation, visual consistency, and a comprehensive range of features tailored to user needs. This research aims to design the UI/UX of an e-commerce application for the Roda Mas workshop using a User-Centered Design (UCD) approach, which places the user at the center of the design process. The prototype was designed using Figma and validated through Maze testing to obtain metrics such as task success rate, time on task, and error rate. Additionally, a System Usability Scale (SUS) questionnaire was administered to measure user perceptions of the resulting design. The results of this research are expected to produce a design prototypr that is not only functional and aesthetic, but also easy to use, meets costumer needs, and can serve as a basis for developing more effective digital applications in the future.